The transformation we need is:
Translate triangle A 1 unit up and 1 unit to the left, rotate it 90° clockwise about the origin, and reflect it over the y-axis. Therefore the answer is C.
This comes from the following facts.
A translation 1 unit up and 1 unit to the left is given by:
![(x,y)\rightarrow(x-1,y+1)](https://img.qammunity.org/2023/formulas/mathematics/college/13872hfxd2chn6wwun2koyayo3qz9mxkh0.png)
Then the original vertexes take the form:
![\begin{gathered} (-3,-1)\rightarrow(-4,0) \\ (-3,-5)\rightarrow(-4,-4) \\ (-1,-5)\rightarrow(-2,-4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8cf168n38z7b51ky4z9e45m834qz47zypw.png)
Now, we make a rotation of 90° clockwise, this is given by:
![(x,y)\rightarrow(y,-x)](https://img.qammunity.org/2023/formulas/mathematics/college/p103kdtjemgzzaskeyeogvxih246rhhmbi.png)
Then we have:
![\begin{gathered} (-3,-1)\rightarrow(-4,0)\rightarrow(0,4) \\ (-3,-5)\rightarrow(-4,-4)\rightarrow(-4,4) \\ (-1,-5)\rightarrow(-2,-4)\rightarrow(-4,2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9mc40ybu1ql3d0rm88eyvfj1hxfgs4gcao.png)
Finally we make a reflection over the y-axis, this is given by:
![(x,y)\rightarrow(-x,y)](https://img.qammunity.org/2023/formulas/mathematics/college/ikcitr9ov18gnuy0131ezdtc936qt485rg.png)
Then we have:
![\begin{gathered} (-3,-1)\rightarrow(-4,0)\rightarrow(0,4)\rightarrow(0,4) \\ (-3,-5)\rightarrow(-4,-4)\rightarrow(-4,4)\rightarrow(4,4) \\ (-1,-5)\rightarrow(-2,-4)\rightarrow(-4,2)\rightarrow(4,2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/u5jhuj5c0dem06fn9qva2rt1npwws1rmgu.png)
Therefore the whole transformation is:
![\begin{gathered} (-3,-1)\rightarrow(0,4) \\ (-3,-5)\rightarrow(4,4) \\ (-1,-5)\rightarrow(4,2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o7a46shysitbmc304iyznyjvhqvzbhhue9.png)
And we notice that this transformation takes triangle A onto triangle B.